2004
DOI: 10.1016/j.jacc.2004.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indexes in relation to target organ damage in high-risk hypertensive patients

Abstract: Patients with hypertension have evidence of changes in platelet physiology, as reflected by a higher level of pP-sel. Patients with TOD also had larger platelets, with greater mass, and the use of aspirin lowered pP-sel and sP-sel levels. These changes may have implications for the pathophysiology of cardiovascular and cerebrovascular disease in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 45 publications
4
110
0
Order By: Relevance
“…Soluble ICAM-1 and VCAM-1 have also been explored in the context of essential hypertension. [26][27][28][29][30][31] In this study, ICAM-1 and VCAM-1 concentrations before RSD were significantly higher in patients who responded to RSD. Shear stress and endothelial cell activation stimulate the expression of ICAM-1 and VCAM-1 during essential hypertension, suggesting that the endothelium is more activated in responders than in nonresponders, although baseline systolic BP did not significantly differ between responders and nonresponders.…”
Section: Discussionmentioning
confidence: 87%
“…Soluble ICAM-1 and VCAM-1 have also been explored in the context of essential hypertension. [26][27][28][29][30][31] In this study, ICAM-1 and VCAM-1 concentrations before RSD were significantly higher in patients who responded to RSD. Shear stress and endothelial cell activation stimulate the expression of ICAM-1 and VCAM-1 during essential hypertension, suggesting that the endothelium is more activated in responders than in nonresponders, although baseline systolic BP did not significantly differ between responders and nonresponders.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies have reported a relationship between MPV and hypertension in different patient groups. Nadar et al [15] demonstrated that hypertensive patients with target organ damage including stroke, previous MI, angina microalbuminuria/proteinuria, and left ventricular hypertrophy, had higher MPV levels than hypertensive patients without target organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the blood coagulation factors, it has been clearly demonstrated that PB administration causes prolongation of APTT, which is dependent on vitais not observed (Bouwman et al, 1999; Mochizuki et al PCT was noted in both sexes treated with 80 mg/kg/day -cant decrease in the MPM and PMDW with no alterations in the MPV and MPC was observed in rats of both sexes treated with either dose of PB. The analysis of platelet indices indicated that the administration of PB increases the number of platelets with a small mass in the absence of platelet activation (Nadar et al, 2004). Although an increase in the PLT appears to be an associated change was observed only in females at 80 and 8.0 mg/kg/day, but it was unlikely that these changes were biologically…”
Section: Hematopoietic Toxicitymentioning
confidence: 96%